(untitled) (Physical Education, Health and Social Sciences, 2025)
This study analyzes the concept of Trauma-Informed Care (TIC) in nursing practice. Background: Growing awareness of trauma’s impact, healthcare systems are adopting TIC to enhance patient-centered care. Nursing plays a key role in fostering safety, trust, and empowerment for trauma-affected individuals. Aims: Despite increasing focus on TIC, its attributes, antecedents, and consequences remain unclear in nursing. A concept analysis is needed to define and understand its role in practice. Methods: Walker and Avant’s approach was used to examine TIC’s defining attributes, antecedents, and consequences. Results: Key attributes of TIC include (1) recognizing trauma’s impact, (2) ensuring safety, trust, and collaboration, and (3) promoting patient empowerment. Antecedents include provider education, institutional policies, and trauma awareness, while consequences lead to better patient outcomes, stronger therapeutic relationships, and reduced healthcare disparities. Discussion: This study integrates psychological and nursing theories, emphasizing a holistic approach that includes individual competencies and systemic changes for effective TIC implementation. Conclusion & Implications: Findings support nursing education, policy development, and clinical practice improvements. Nurse leaders and policymakers can use these insights to establish training programs and trauma-sensitive healthcare environments.